Biological implications of coeruleospinal inhibition of nociceptive processing in the spinal cord - Tsuruoka, Masayoshi; Tamaki, Junichiro (Frontiers in Integrative Neuroscience, 2012)
The coeruleospinal inhibitory pathway (CSIP), the descending pathway from the nucleus locus coeruleus (LC) and the nucleus subcoeruleus (SC), is one of the centrifugal pain control systems. This review answers two questions regarding the role coeruleospinal inhibition plays in the mammalian brain. First is related to an abnormal pain state, such as inflammation. Peripheral inflammation activated the CSIP, and activation of this pathway resulted in a decrease in the extent of the development of inflammatory hyperalgesia. During inflammation, the responses of the dorsal horn neurons to graded heat stimuli in the LC/SC-lesioned rats did not produce a further increase with the increase of stimulus intensity in the higher range temperatures. These results suggest that the function of CSIP is to maintain the accuracy of intensity coding in the dorsal horn because the plateauing of the heat-evoked response in the LC/SC-lesioned rats during inflammation is due to a response saturation that results from the lack of coeruleospinal inhibition. The second concerns attention and vigilance. During freezing behavior induced by air puff stimulation, nociceptive signals were inhibited by the CSIP. The result implies that the CSIP suppresses pain system to extract other sensory information that is essential for circumstantial judgment.